The Effect of Online Learning on Mathematical Communication Ability in 10th Grade Senior High School - Faisol Hidayatulloh; Faridatun Nurus Sholihah; Eliza Verdianingsih (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The current Covid-19 pandemic has disrupted the conventional learning process which had been done face-to-face. So a solution is needed to answer this problem. Online learning is one alternative that can overcome this problem. The purpose of this study was to determine the mathematical communication skills of students at State High School 3 Jombang, which during this pandemic had an online learning process. The subjects of this study were students of class 10th MAN 3 Jombang. The data were collected by giving a test in the form of 3 essay questions, giving a questionnaire and an interview. The analysis was carried out using the One Sample T-test technique and the results showed that the t-count values ​​in the description test and questionnaire were 35,327 and 102,384, respectively, with a significance of 0.000. The significance value shows 0.000 < 0.05, then Ho is rejected and Ha is accepted, meaning that there is a significant effect of online learning on the mathematical communication skills of class 10th MAN 3 Jombang